2016
DOI: 10.1021/acs.joc.6b00231
|View full text |Cite
|
Sign up to set email alerts
|

Domino Synthesis of Tetrasubstituted Thiophenes from 1,3-Enynes with Mercaptoacetaldehyde

Abstract: Domino synthesis of tetrasubstituted thiophenes is described from 1,3-enynes and mercaptoacetaldehyde using DABCO at room temperature via a Michael addition, 5-exo-dig carboannulation, and oxidation sequence under air. The broad substrate scope and mild reaction conditions are significant practical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Furthermore, the use of 1‐nitro‐1,3‐enynes in sequential catalytic reactions that combine metal catalysis and organocatalysis to generate pyrano‐annulated pyrazoles and tetrahydrofuranyl derivatives was reported by Enders and Krause/Alexakis, respectively. The use of ( E )‐2‐nitro‐1,3‐enynes for the synthesis of highly substituted pyrroles and thiophenes has been reported by Punniyamurthy. The pyrano‐annulated molecular architectures can be readily assembled by using ( E )‐2‐nitro‐1,3‐enynes in organocatalytic tandem reactions via in situ formation of an allene (Scheme , eqs a and b) .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the use of 1‐nitro‐1,3‐enynes in sequential catalytic reactions that combine metal catalysis and organocatalysis to generate pyrano‐annulated pyrazoles and tetrahydrofuranyl derivatives was reported by Enders and Krause/Alexakis, respectively. The use of ( E )‐2‐nitro‐1,3‐enynes for the synthesis of highly substituted pyrroles and thiophenes has been reported by Punniyamurthy. The pyrano‐annulated molecular architectures can be readily assembled by using ( E )‐2‐nitro‐1,3‐enynes in organocatalytic tandem reactions via in situ formation of an allene (Scheme , eqs a and b) .…”
Section: Methodsmentioning
confidence: 99%
“…[51] The broad substrate scope and mild reaction conditions are significant and practical features, but the main advantages of this sequence are the direct introduction of aldehyde and NO 2 /COPh/CO 2 Et functionalities on the thiophene ring under metal-free and mild conditions. [51] The broad substrate scope and mild reaction conditions are significant and practical features, but the main advantages of this sequence are the direct introduction of aldehyde and NO 2 /COPh/CO 2 Et functionalities on the thiophene ring under metal-free and mild conditions.…”
Section: Synthesis Of Thiophenesmentioning
confidence: 99%
“…More recently (Scheme 23), the same group described the preparation of tetrasubstituted thiophenes 68 from 1,3-enynes 67 and 1 in the presence of DABCO at room temperature, in a domino reaction sequence involving Michael addition, 5-exodig carboannulation and oxidation under air. [51] The broad substrate scope and mild reaction conditions are significant and practical features, but the main advantages of this sequence are the direct introduction of aldehyde and NO 2 /COPh/CO 2 Et functionalities on the thiophene ring under metal-free and mild conditions. Scheme 23.…”
Section: Synthesis Of Thiophenesmentioning
confidence: 99%
“…carbaldehydes through a reaction between 1,3-enynes and 1,4-dithiane-2,5-diol in the presence of DABCO (Scheme 1, equation III). 10 Very recently, Deng et al have reported a one-pot synthesis of 2,3,5-trisubstituted thiophenes through the three-component assembly of arylacetaldehydes, 1,3-dicarbonyl compounds, and elemental sulfur (Scheme 1, equation IV). However, the α,β-unsaturated aldehyde, acrolein, did not afford the corresponding thiophene upon treatment with 2,4-pentanedione under the standard conditions (Scheme 1, equation V).…”
Section: Letter Syn Lettmentioning
confidence: 99%